Transfer Ribonucleic Acid Nucleotidyltransferase and Transfer Ribonucleic Acid in Sendai Virions - Kolakofsky, Daniel (1972)
Sendai virions contain both transfer ribonucleic acid (tRNA) nucleotidyltransferase and its substrate, tRNA missing its CCA-OH end.